1994
DOI: 10.3109/02844319409022008
|View full text |Cite
|
Sign up to set email alerts
|

Topical Zinc Oxide Treatment Increases Endogenous Gene Expression of Insulin-Like Growth Factor-1 in Granulation Tissue from Porcine Wounds

Abstract: Application of zinc oxide has been shown to accelerate the healing of both chronic and acute wounds, but the mechanisms are unknown. We quantified the gene expression (mRNA) for one important growth factor, insulin-like growth factor-1 (IGF-1) in 12 full-thickness wounds in each of three domestic pigs treated with or without topical zinc oxide. We used a RNAase protection/solution hybridisation technique to measure IGF-1 mRNA concentrations, which were 50% higher in the granulation tissue in wounds treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Experiments have been carried out in nutritionally balanced domestic pigs to substantiate the therapeutic value of zinc oxide supplement in wound healing and its putative mechanisms of action 126 . We could demonstrate 30% promotion of healing by topical zinc oxide in both partial‐thickness and full‐thickness wounds 126–128 . Whereas supplementary zinc oxide advanced epithelialization significantly in these experiments, topical zinc sulfate offered no benefits on wound healing (Figure 1).…”
Section: Zinc In Wound‐healing Physiologymentioning
confidence: 85%
“…Experiments have been carried out in nutritionally balanced domestic pigs to substantiate the therapeutic value of zinc oxide supplement in wound healing and its putative mechanisms of action 126 . We could demonstrate 30% promotion of healing by topical zinc oxide in both partial‐thickness and full‐thickness wounds 126–128 . Whereas supplementary zinc oxide advanced epithelialization significantly in these experiments, topical zinc sulfate offered no benefits on wound healing (Figure 1).…”
Section: Zinc In Wound‐healing Physiologymentioning
confidence: 85%
“…Meanwhile, the concentration is sufficient for wound healing effects. [5][6][7][8] The increasing interest in aqueous colloidal nanogels or microgels 9 in the past decades is due to many useful applications such as coatings, agriculture, medicine, etc., which a)…”
Section: Introductionmentioning
confidence: 99%
“…32 Additionally, studies have demonstrated the ability of topical zinc oxide to enhance healing in skin. 33,34 This skin protectant is effective for prophylaxis or treatment of mild diaper dermatitis, but when the involved skin is more severely affected, an antifungal agent and low-potency topical corticosteroid such as hydrocortisone may be used as well. 24 However, as previously discussed, current antifungal-corticosteroid combination preparations contain potent, halogenated corticosteroids that are contraindicated for use in diaper dermatitis.…”
Section: Methodsmentioning
confidence: 99%